The relationship between learning organizations characteristics and critical success factors: دراسة تحليلية لآراء عينة من القيادات والعاملين في رئاسة جامعة الكوفة - باسمه محمد باني الزرفي (Iraqi Journal for Administrative Sciences, 2024)
Study builds recognize the reality of the University of Kufa in terms of adoption of the concept of learning organizations. And make recommendations that will improve the performance of the university on the development of knowledge and intellectual capital, and the importance of the study of the importance of universities and large responsibility of higher education and out of modern management attention directed towards Knowledge intellectual Capital, Learning organization was used as a tool for measuring the characteristics of a questionnaire, the study sample consisted of (61)Human resource members of the university leaders, faculty, staff and staff at the university level body exclusively and its departments, Data was analyzed using percentages and averages, and analysis of variance. The results showed that the adoption of the characteristics of a learning organizations are (promoting cooperation and learning through the group, linked to the organization of Foreign surrounding environment, enabling workers toward a common vision, strategic leadership in support of learning, providing opportunities for continuous learning, encourage dialogue and discussion, the establishment of a knowledge sharing and learning systems). The critical success factors in the study offered a learning organization at least the characteristics of an application at the university and that call for a movement organized and quickly by the university to improve the rates of those characteristics as well as to view the most characteristics in application, which can be invested, pushing the university toward learning and build a learning organization and invest their capital in those characteristics, Where there is an urgent necessity makes it imperative for organizations working to follow a specific methodology for continuous learning The study found a set of conclusions and recommendations, Including high averages of paragraphs variable (CSFs), These results indicate that workers at the University of Kufa responses on these variables was the (positive), and the level of assessment of the paragraphs of this variable was (high) from the perspective of workers in the mentioned university. The study found, to provide senior leadership in every organization support CAF for all employees in different job categories to connect with learning through their participation in conferences, seminars and training programs varied for the purpose of encouraging individual and collective learning as well as the regulatory environment appropriate to provide for learning and reward workers who participated in the conference events, or who have received the rehabilitation of scientific best. .Key words: learning organization, promoting cooperation, empowering workers, encourage dialogue, critical factors, Kufa University.